Toys scooper / Jannyah Jaafar - Jaafar, Jannyah (Universiti Teknologi MARA, Kedah, 2019)
Normally after playing toys children have a problem to clean it up. All those tiny pieces of toys, all the ways they could get lost, or stuck in the carpet. So this ToyS Scooper will help us to solve the problem at home. This product is an invention from a group of children who used mind storm programming and sensors to count the toys pieces and will help to differentiate colours. It is user friendly and easy to carry.